Dispersion Simulations of Radon Discharges between Neighboring Buildings and Their Sensitivity to Meteorology, Discharge Rate, and Building Geometry. Issue 3 (March 2022) - Lebel, Luke; John, Aneesh; Korolevych, Volodymyr
Abstract : Abstract: In northern climates, it is common to install the discharges of radon sub-slab depressurization systems near ground level. However, this also elevates the ground level outdoor radon concentrations and raises the possibility of radon re-entrainment into homes. The study aims to assess outdoor radon concentrations near above-ground-level discharges along the surfaces of an emitting building and its close neighbor and identify parameters that most influence the dilution. This study employs a series of computational fluid dynamics calculations to assess concentrations along the exhaust-facing and non-exhaust-facing surfaces of the buildings. Different meteorological, venting, and building geometry parameters are explored. Boundary conditions for the CFD calculations are based on field measurements of the ground-level wind speeds and seasonal air temperatures and atmospheric stabilities. Outdoor concentrations can be as high as 7% of the discharge gas, although these become smaller at greater distances from the vent. The direction of the prevailing wind is a particularly important parameter, as it influences the formation of circulating building cavities and building wakes where radon could accumulate. The wind speed, atmospheric stability, and season (plume buoyancy) also have important influences on the outdoor radon concentrations, as do the velocity of the vent system and the size of the buildings. The study has assessed the dilution of the radon-laden exhaust gas and determined the outdoor concentrations that can be expected under a variety of conditions. These results can be used to inform regulators about the potential for radon re-entrainment into homes.